Cálculo riguroso y termodinámicamente consistente de equilibrio líquido-vapor en sistemas binarios isotérmicos. - Mora Casal, René (2016)
A rigorous method for calculating thermodynamically consistent vapor composition data in isothermal binary systems is fully developed. The method does not require the simplifying assumptions of ideal gas and negligible liquid volume and the result is a first-order differential equation for